Effect of carbon molecular sieve sizing with poly(vinyl pyrrolidone) K-15 on carbon molecular sieve–polysulfone mixed matrix membrane - W. A. W., Rafizah (Elsevier B.V., 2008)
Mixed matrix membranes (MMMs) comprising polysulfone (PSF) Udel® P-1700 and 30 wt% carbon molecular sieve (CMS) particles (<25 μm) have been fabricated and characterized. CMS particles were treated in poly(vinyl pyrrolidone) kollidone 15 (PVP K-15) sizing bath solution (1–10 wt% in isopropanol) prior to embedment into the matrix solution to improve matrix–sieve interfacial adhesion. This study investigated the effects of CMS sizing with PVP K-15 on the morphology and the gas separation performance of PSF–CMS MMMs. The fabricated MMMs were characterized using TGA, DSC, FESEM, ATR-FTIR and single gas permeation test using high purity O2 and N2. A dramatic improvement in CMS–PSF adhesion was observed using FESEM micrographs upon incorporation of PVP K-15-sized CMS particles. ATR-FTIR results suggest the occurrence of intermolecular interaction between PVP K-15 sizing layer on the outer surface of CMS particles and PSF matrix. A substantial recovery of separation performance was achieved whereby the PSF–PVP-sized CMS MMM exhibited 1.7 times higher O2/N2 selectivity compared to that of unmodified MMM